Writing Reaction Mechanisms in Organic Chemistry. - Miller, Audrey (Elsevier, 1999)
Sex Differences serves as an advanced text for courses in evolutionary and human biology, psychology, and sexuality and gender studies. It also serves as a reference source for academic professionals in these disciplines. The book covers the evolution of sex and sex differences, and sex differences and sexual strategies in non-human and human animals. The final chapter addresses issues of sex and gender in interpersonal relationships, organizations and politics. Diagrams, graphs, charts, and tables illustrate key concepts; cartoons and photos provide visual breaks and an element of humor.